Submicron-scale Au-decorated TiO2 mesoporous spheres for enhanced photon harvesting in DSSCs through near-field enhancement, light scattering, and dye loading - Joshi, Dhavalkumar N.; Pal, Anil Kumar; Krishnapriya, R.; Arun Prasath, R. (Frontiers in Materials, 2024)
Light harvesting materials are crucial for capturing the sunlight in a device such as a solar cell for better efficiency. In this study, we developed high surface area, submicron-sized TiO2 spheres (MTS) incorporated with anisotropic Au nanoparticles (Au_MTS) to create highly light-absorbing photoanodes for enhanced dye-sensitized solar cell (DSSC) efficiency. The high surface area of MTS (~125 m²/g) allows for increased dye-loading, while their submicron size (150-300 nm) provides superior light-scattering capabilities for significantly enhancing the photoanode's light absorption. Furthermore, incorporating of anisotropic Au nanoparticles enables broadband surface plasmon resonance (SPR) coupling, synergistically boosting photon harvesting in the Au_MTS photoanodes. The interconnected tiny TiO2 nanoparticle network in MTS supports charge carrier generation and transport, providing ample sites for dye adsorption and efficient electron pathways. Au_MTS with varying amounts of Au nanoparticles synthesized by a greener microwave-assisted synthesis method and DSSC devices were fabricated and compared with devices made from pristine MTS and P25 nanoparticles. The optimal Au_MTS device, containing ~1.3 wt.% Au nanoparticles, achieved a maximum power conversion efficiency (PCE) of ~7.7%, representing improvements of ~40% and ~60% over pristine MTS (PCE of ~5.2%) and P25 nanoparticles (PCE of ~4.71%), respectively. Overall, this work demonstrates the effectiveness of plasmonic mesoporous photoanodes in enhancing DSSC performance through improved photo response, light scattering, and dye loading.